A high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film and its preparation method.
Patent Information
- Application Number
- CN202610830736.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-27
AI Technical Summary
本发明的目的在于克服现有LDPE/LLDPE共混地膜界面相容性差、力学性能不足、断裂标称应变偏低、撕裂负荷偏小、耐候老化性能差、无法稳定达到国家高强度地膜标准等缺陷,提供一种高韧性耐老化方便回收的增强型农用地面覆盖薄膜及其制备方法,使地膜产品全面达到并超越国标加厚高强度地膜的全部技术指标,同时具备优异的耐候性能和可回收性能
[0003]3.1 要解决的技术问题
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of new polymer agricultural film materials, specifically to a multi-component material system design using low-density polyethylene (LDPE) as the matrix and linear low-density polyethylene (LLDPE) as the reinforcement. This system incorporates POE elastomer interfacial compatibilization, binary nano-synergistic reinforcement, and five-layer synergistic weather protection, resulting in an enhanced agricultural ground cover film with ultra-high mechanical properties, efficient weather resistance and anti-aging properties, and good recyclability, as well as its preparation method. Background Technology
[0002] Low-density polyethylene (LDPE) is the core base resin for agricultural mulch film production. It boasts significant advantages such as convenient molding and processing, excellent blown film forming properties, superior film bubble stability, smooth and glossy film, high appearance quality, and controllable raw material costs (approximately 8,000–9,000 RMB / ton). Furthermore, it is fully compatible with the process window of general blown film equipment, indicating a high degree of industrial maturity. However, due to the inherent characteristics of LDPE's molecular chain structure—a large number of long branches, widespread random distribution, and relatively low crystallinity—the chain entanglement density and stress transfer efficiency within the polymer matrix are relatively insufficient. This results in pure LDPE mulch films generally exhibiting poor mechanical properties, weak puncture and tear resistance, and low resistance to environmental aging, making it difficult to meet the stringent requirements of modern agriculture for high-intensity, long-cycle, and mechanized mulching operations. Linear low-density polyethylene (LLDPE) has high molecular chain linearity and uniform short branch distribution, and has excellent molecular chain entanglement ability, puncture resistance and tear resistance. It is the preferred blending modification material for mechanical reinforcement of polyethylene film. However, existing industrial LDPE / LLDPE binary blended mulch films generally have common problems such as unreasonable ratio design, poor interfacial compatibility and uneven dispersion of additives. The products are prone to defects such as significant anisotropy of the film, imbalance of longitudinal and transverse mechanical properties, insufficient elongation at break and rapid decay of aging resistance. They have always failed to meet the comprehensive requirements of the national thickened high-strength mulch film rigidity index. For example, Huo Chang'an et al.
[11] studied the mechanical properties of LDPE / LLDPE blended films with different ratios (30:70 to 70:30). The results showed that when the LDPE content exceeded 50%, the tensile strength of the film decreased significantly, and the difference in longitudinal and transverse properties increased with the deviation of the ratio. According to the mandatory technical requirements for thickened high-strength mulch films in the current national standard GB 13735-2017 "Polyethylene Blown Agricultural Ground Cover Film", the longitudinal tensile load must be ≥3.6N, the transverse tensile load must be ≥3.2N, the longitudinal nominal strain at break must be ≥550%, the transverse nominal strain at break must be ≥700%, the longitudinal right-angle tear load must be ≥1.6N, and the transverse right-angle tear load must be ≥1.8N. Commonly available LDPE / LLDPE blend mulch films generally suffer from insufficient tensile load, low elongation at break, imbalance in longitudinal and transverse properties, brittleness, and substandard tear load. A more prominent problem is that, due to insufficient mechanical strength and poor weather resistance, traditional plastic film develops large-scale cracking, fragmentation, and powdering in the later stages of use, making it impossible to remove in its entirety after use. According to data from the Ministry of Agriculture and Rural Affairs, the amount of residual film in the topsoil of some long-term mulched farmland in my country has reached 15-25 kg per mu (approximately 0.067 hectares). Once mixed with the soil, the film fragments are extremely difficult to separate, not only damaging the soil aggregate structure and hindering the transport of water and nutrients, but also physically obstructing crop root development, resulting in serious "white pollution" in farmland. Current mechanized residual film recycling equipment has strict requirements on the integrity and minimum strength of the film—the tensile strength of the film surface must be ≥2.5 MPa, and the single-removal length must be ≥3 m for it to be effectively grasped and rolled up by existing rake-type or shovel-type recycling machinery. However, traditional plastic film develops numerous micro-cracks after only 3-6 months of use, breaking easily when pulled during removal, failing to meet the basic conditions for mechanized recycling. Meanwhile, the weather resistance and anti-aging system of traditional LDPE / LLDPE blended mulch film is designed in a simple way, usually adding only one or two types of light stabilizers. It is difficult to effectively protect against multiple aging factors such as ultraviolet radiation, high temperature oxidation, diurnal temperature difference, humidity change, and wind and sand erosion in the complex and ever-changing field exposure environment. The effective service life of ordinary mulch film is generally only 6 to 8 months. In summary, there is an urgent need to develop a differentiated resin compound system with a high proportion of LDPE as the matrix and a low proportion of LLDPE as the reinforcement. This system should systematically address the aforementioned traditional technical challenges through an integrated modification strategy that combines interfacial compatibilization, multi-component nano-synergistic reinforcement, and multi-level weather protection. Summary of the Invention
[0003] 3.1 Technical problems to be solved The purpose of this invention is to overcome the shortcomings of existing LDPE / LLDPE blended mulch films, such as poor interfacial compatibility, insufficient mechanical properties, low nominal strain at break, low tear load, poor weather resistance and aging resistance, and inability to consistently meet national high-strength mulch film standards. This invention provides a high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film and its preparation method, enabling the mulch film product to fully meet and exceed all the technical indicators of national standard thickened high-strength mulch films, while also possessing excellent weather resistance and recyclability. 3.2 Technical Solution To achieve the above objectives, the present invention adopts the following technical solution: A high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film is prepared from the following raw materials in parts by weight: 78-85 parts of low-density polyethylene resin (LDPE), 10-16 parts of linear low-density polyethylene resin (LLDPE), 1.2-2.0 parts of POE elastomer toughening agent, 1.0-1.8 parts of activated nano-silica, 1.0-1.6 parts of ultrafine active talc, 0.10-0.20 parts of low-temperature dispersing lubricant, 0.18-0.28 parts of antioxidant 1010, 0.12-0.20 parts of auxiliary antioxidant 168, 0.22-0.32 parts of high-molecular-weight hindered amine stabilizer 944, 0.18-0.24 parts of antioxidant zinc composite heat stabilizer, 0.10-0.14 parts of silane coupling agent KH-560, and 0.10-0.16 parts of dispersing brightener. As a preferred embodiment, the weight ratio of each raw material is as follows: 82 parts LDPE, 13 parts LLDPE, 1.6 parts POE elastomer toughening agent, 1.4 parts activated nano silica, 1.2 parts ultrafine active talc, 0.15 parts low-temperature dispersing lubricant, 0.24 parts antioxidant 1010, 0.16 parts auxiliary antioxidant 168, 0.26 parts high molecular weight hindered amine stabilizer 944, 0.20 parts antioxidant zinc composite heat stabilizer, 0.12 parts silane coupling agent KH-560, and 0.13 parts dispersing brightener. The preparation method includes the following steps: (1) Nanofiller activation pretreatment: Activated nano silica and ultrafine active talc powder are mixed according to the ratio, and metered silane coupling agent KH-560 and dispersing brightener are added. The mixture is activated by high-speed stirring at 68-72℃ for 18-22 min to fully complete the surface activation modification. The residual moisture and volatiles are removed by low-temperature drying; (2) Precision preparation of composite additives: Low-temperature dispersing lubricant, antioxidant 1010, auxiliary antioxidant 168, polymer hindered amine stabilizer 944, and antioxidant zinc composite heat stabilizer are prepared. After weighing the proportions precisely, stir evenly; (3) Pretreatment of resin matrix: put LDPE resin, LLDPE resin and POE elastomer toughening agent into a high-speed mixing device and stir at room temperature for 5-7 minutes; (4) Multi-component blending: add the materials obtained in step (1) and step (2) to the mixture obtained in step (3) in sequence and stir at room temperature for 8-10 minutes; (5) Melt extrusion blow molding: control the barrel temperature in sections at 155-175℃, extrude through the die head and cool and shape with an air ring; (6) Biaxial stretching and traction and leveling and winding. 3.3 Innovations of this invention (1) Innovation of Differentiated Matrix Resin Blending System: A differentiated blending system is adopted, using high-proportion LDPE (78-85 parts) as the matrix and low-proportion LLDPE (10-16 parts) as the toughening and reinforcing body. Agricultural mulch film grade LDPE with a melt flow rate of 2.0 g / 10 min and film grade LLDPE with a melt flow rate of 1.8 g / 10 min are selected. By controlling the melt viscosity ratio of the two to be within the optimized range of 1.1:1, the two components form a "sea-island" microstructure with LDPE as the marine phase and LLDPE as the island phase during the blending process. The continuous LDPE phase ensures excellent molding processability and film surface smoothness, while the dispersed LLDPE phase provides a mechanical reinforcing skeleton due to the high entanglement density of its linear polymer chains. This ratio range simultaneously ensures the structural integrity of the continuous LDPE phase (LLDPE proportion not exceeding 16% to avoid phase inversion) and the minimum effective density of the LLDPE reinforcing phase (LLDPE proportion not less than 10% to ensure the formation of a percolation network in the matrix). (2) Innovation in POE interface compatibilization and dispersion toughening: Micron-sized POE (ethylene-octene copolymer) elastomer toughening agent was introduced as a compatibilizing and modifying medium for the LDPE / LLDPE interface. The flexible segments provided by the octene comonomer in POE are thermodynamically compatible with the linear segments of LLDPE, while the ethylene main chain segments overlap with the LDPE matrix in the crystallization temperature range (both 105-115℃). During melt blending and cooling crystallization, POE molecular chains can simultaneously insert into the interface between the LDPE and LLDPE phases to form a flexible transition layer. Orthogonal synergistic experiments confirmed that there is a significant positive synergistic effect between POE compatibilization and nanofillers (synergistic index SI=1.36), and the nominal transverse fracture strain (795%) when both work together far exceeds the simple sum of their individual contributions. (3) Multi-component nano-precision reinforcement innovation: A "sphere-sheet" binary composite reinforcement system is adopted, consisting of activated nano-silica (spherical, D50≈30nm) and ultrafine activated talc (lamellar, lamellar thickness <100nm). After surface activation with silane coupling agent KH-560, the compatibility between nanoparticles and polyethylene matrix is significantly improved. Spherical SiO2 achieves both reinforcement and toughening through the "nanoparticle pinning effect"; the lamellar talc is oriented and arranged along the film surface during blow molding and stretching to form a "maze effect", which improves puncture resistance and gas barrier properties. (4) Five-layer synergistic weather protection innovation: Constructing a five-layer integrated molecular chain protection system consisting of "hindered amine free radical cyclic capture (HALS 944) + hindered phenol main antioxidant (AO 1010) + phosphite auxiliary antioxidant (AO 168) + nano zinc oxide UV shielding and metal passivation + silane coupling agent interface stabilization (KH-560)". The five layers comprehensively block the breakage of polyethylene molecular chains from three degradation pathways: photo-initiated, thermally initiated, and catalytically initiated. Multi-time point aging experiments confirmed that Example 1 showed a stable decay rate (0.013~0.027% / h) throughout the 500h aging range, with no autocatalytic degradation inflection point, while pure LDPE mulch film showed an accelerated decay inflection point in the 200~300h range. (5) Material system design drives innovation in recycling performance: Starting from the first principles of polymer materials science, a causal chain of "material design → durability → recycling feasibility" is established. By compounding the matrix resin to provide a basic strength skeleton, increasing the compatibilization of POE to eliminate weak points at the interface and giving it high elongation, enhancing the tear resistance threshold with binary nano-reinforcement, and delaying molecular chain degradation with five-layer weather protection, the mulch film can maintain its molecular chain structure, prevent embrittlement and powdering, and maintain balanced longitudinal and transverse strength after 13 to 16 months of field service. This internalizes "recycling convenience" as an inherent property of the material system, fundamentally solving the dilemma of farmland residual film recycling. 3.4 Description of the attached figures The core of the technical solution of this invention lies in the raw material composition, proportioning, and process parameters. Performance test data for each embodiment and comparative example are presented in tabular and graphical form. This application is accompanied by… Figures 1 to 4 This document presents aging performance degradation curves at multiple time points, radar comparison charts of orthogonal synergistic effects, and quantitative analysis charts of the synergistic effect index. It is recommended to commission a third-party testing agency to supplement SEM cross-sectional microstructure comparison photos and DSC crystallization behavior comparison curves before formal submission.
[0004] 4.1 Material System Design Concept This invention, from the perspective of polymer materials engineering, utilizes a multi-component, multi-scale, and multi-functional material synergistic design to enable the mulch film to simultaneously meet the dual requirements of "high strength and high durability during service" and "complete recyclability after decommissioning." The design concept follows a progressive triple-protection logic chain: The first layer – the strength skeleton: high proportion of LDPE provides sufficient molding processability and matrix continuity, while the linear molecular chains of LLDPE provide the basic reinforcing skeleton. After being compatibilized by the POE interface, the two form a continuous phase structure with molecular-level interpenetration, laying the foundation for high strength and high elongation. The second layer—the tear-resistant barrier—is a "sphere-plate" binary reinforcement system composed of activated nano-SiO2 (spherical, 30-50nm) and ultrafine active talc powder (lamellar). This system enhances the material's resistance to crack initiation and propagation in both three-dimensional space and two-dimensional plane, effectively blocking localized damage to the membrane surface caused by field sand and gravel impacts, mechanical friction, and alternating wind stress, preventing micro-damage from accumulating and evolving into through-cracks. The third layer – molecular chain protection: a five-level synergistic protection network consisting of hindered amine 944 + hindered phenol 1010 + phosphite 168 + nano ZnO + KH-560, simultaneously blocks the breakage and degradation of polyethylene molecular chains through three pathways: photo-initiated, thermally initiated, and catalytically initiated, maximizing the preservation of the molecular weight and mechanical integrity of the polymer chains at the end of their service life. 4.2 Raw material formulation This invention provides a highly tough, aging-resistant, and easily recyclable reinforced agricultural ground cover film, prepared from the following raw materials in parts by weight: Low-density polyethylene resin (LDPE): 78-85 parts; Linear low-density polyethylene resin (LLDPE): 10-16 parts; POE elastomer toughening agent: 1.2–2.0 parts; Activated nano-silica: 1.0–1.8 parts; Ultrafine active talc: 1.0–1.6 parts; Low-temperature dispersible lubricant: 0.10–0.20 parts; Antioxidant 1010: 0.18–0.28 parts; Antioxidant 168: 0.12–0.20 parts; High molecular weight hindered amine stabilizer 944: 0.22–0.32 parts; Antioxidant zinc composite heat stabilizer: 0.18–0.24 parts; Silane coupling agent KH-560: 0.10–0.14 parts; Dispersing brightener: 0.10 to 0.16 parts. 4.3 Optimal Formula As a preferred embodiment of the present invention, the weight proportions of each raw material are as follows: Low-density polyethylene resin (LDPE): 82 parts; Linear low-density polyethylene resin (LLDPE): 13 parts; POE elastomer toughening agent: 1.6 parts; Activated nano-silica: 1.4 parts; Ultrafine active talc: 1.2 parts; Low-temperature dispersible lubricant: 0.15 parts; Antioxidant 1010: 0.24 parts; Antioxidant 168: 0.16 parts; hindered amine stabilizer 944: 0.26 parts; Antioxidant zinc composite heat stabilizer: 0.20 parts; Silane coupling agent KH-560: 0.12 parts; Dispersing brightener: 0.13 parts. 4.4 Raw material specifications The LDPE resin is a special grade resin for agricultural mulch films, with a melt flow rate of 2.0 g / 10 min (190℃ / 2.16 kg), good melt flow uniformity, and excellent blown film stability, film surface flatness, and dimensional consistency. The LLDPE is a film-grade polyethylene resin with a melt flow rate of 1.8 g / 10 min (190℃ / 2.16 kg), high molecular chain linearity, and outstanding puncture and tear resistance. The activated nano-silica and ultrafine activated talc powder have a particle size of 30-50 nm and are surface-activated and modified with silane coupling agent KH-560, resulting in high surface hydrophobicity and significantly improved compatibility with the LDPE / LLDPE matrix. The POE elastomer toughening agent serves as a highly efficient interfacial compatibilizer, effectively improving the interfacial bonding strength of the resin phase interface. 4.5 Mechanism of action of each component and critical values of the ratio range LDPE resin (78-85 parts): As the main substrate of the film, it provides advantages in molding processability, film surface smoothness, and cost. When the LDPE content is less than 78 parts, the film processing fluidity decreases, the film bubble stability deteriorates, and uneven film thickness is prone to occur. When the LDPE content is more than 85 parts, the reinforcing effect of LLDPE is diluted, and the improvement in mechanical properties is insufficient to meet the national standard for high-strength mulch films. 78-85 parts is the optimal balance range that balances processability and mechanical properties. LLDPE resin (10-16 parts): Utilizing its high molecular chain linearity and uniform distribution of short branches, it provides puncture resistance, tear resistance, and toughness enhancement. When the LLDPE content is less than 10 parts, the reinforcing effect is not significant, and the nominal strain at transverse fracture cannot stably reach more than 700% (failure case L1: only 630% when LLDPE=9 parts); when the LLDPE content is more than 16 parts, the processing torque of the blend system increases significantly (failure case L2: torque reaches 125 N·m when LLDPE=20 parts, an increase of 39%), the film surface roughness increases, the blown film bubble breakage frequency is >3 times / hour, and the continuous phase structure of LDPE is destroyed, exacerbating the difference in longitudinal and transverse properties. POE elastomer toughening agent (1.2–2.0 parts): As a compatibilizing and modifying medium at the LDPE / LLDPE two-phase interface, it forms a flexible transition layer at the LDPE and LLDPE phase interface through the molecular motion of its elastomer chain segments, reducing interfacial tension and promoting uniform dispersion and molecular chain entanglement of the two phases. Simultaneously, POE elastomer particles dissipate external stress energy through a "crazing-shear band" mechanism. When the POE content is less than 1.2 parts, the interfacial compatibilization effect is insufficient, and the longitudinal and transverse nominal strain difference at break is >20% (failure case P1: the difference reaches 42% when POE=0.8 parts); when the POE content is greater than 2.0 parts, rigidity decreases, tensile load begins to decline (failure case P2: the longitudinal tensile load drops to 3.2N when POE=2.5 parts), and cost increases significantly. Activated nano-silica (1.0–1.8 parts): After surface activation with silane coupling agent KH-560, the hydroxyl groups on the surface of spherical nano-SiO2 particles are replaced by organic functional groups, changing from hydrophilic to hydrophobic, which greatly improves their compatibility with the polyethylene matrix. They exhibit a nanoscale dispersed distribution in the LDPE / LLDPE matrix, hindering the movement of polymer chain segments through the "nanoparticle pinning effect," thereby increasing modulus and strength. When the dosage is below 1.0 part, the reinforcing effect is not significant; above 1.8 parts, the nanoparticle spacing is less than the critical value (~50 nm), and van der Waals attraction dominates, leading to spontaneous aggregation into micron-sized aggregates (failure example N2: DLS particle size > 800 nm), resulting in stress concentration defects. Ultrafine activated talc (1.0–1.6 parts): This layered silicate structure exhibits excellent interfacial bonding with the matrix after activation. During film blow molding and biaxial stretching, the layers align along the film surface, creating a "maze effect" that enhances the film's puncture resistance and gas barrier properties. Simultaneously, the layered talc forms a "sphere-sheet" binary synergistic reinforcing system with spherical nano-SiO2. At dosages below 1.0 parts, the effect is not significant; above 1.6 parts, the film's light transmittance decreases, affecting crop photosynthesis. Antioxidant system (1010+168): Hindered phenolic primary antioxidant 1010 provides hydrogen atoms to capture peroxide free radicals, blocking chain oxidation reactions; phosphite auxiliary antioxidant 168 decomposes hydroperoxides, preventing them from initiating new free radical chains. The two form a "primary-auxiliary" synergistic effect. When 1010 is below 0.18 parts or 168 is below 0.12 parts, the antioxidant synergistic effect is broken (failure example A1: MFR change rate during processing >30% when AO 1010 = 0.10 parts); when 1010 is above 0.28 parts, phenolic oxidation products cause yellowing of the film surface (failure example A2: transmittance decreases by 12%). Hindered amine stabilizer 944 (0.22–0.32 parts): Through the Denisov cycle mechanism, it repeatedly captures and regenerates free radicals. One molecule of 944 can cycle thousands of times to capture free radicals, making it dozens of times more efficient than traditional UV absorbers. Its high molecular weight (approximately 3,000) structure gives it extremely low migration rate and excellent anti-extraction properties in a polyethylene matrix. When the dosage is below 0.22 parts, long-term photostability is insufficient (failure example H1: retention rate only 72% after 300 hours); above 0.32 parts, marginal benefits decrease and surface precipitation occurs (failure example H2: only a 1.3 percentage point increase, with white bloom on the film surface). Antioxidant zinc composite heat stabilizer (0.18–0.24 parts): This product combines UV shielding and absorption with metal ion passivation. Nano-ZnO particles absorb UV-B wavelengths (280-315 nm), passivating the pro-oxidation activity of residual catalyst metal ions (Ti, Al, etc.) in polyethylene, thus reducing oxidation initiation at its source. It forms an "organic-inorganic" synergistic photostable system with hindered amine 944. UV shielding is insufficient when the dosage is below 0.18 parts, while film transparency is affected when the dosage is above 0.24 parts. 4.6 Raw material sources and brand names The following are recommended sources for each raw material. It should be understood that these sources are for illustrative purposes only and do not constitute a limitation on the scope of protection of this invention: Low-density polyethylene (LDPE): Sinopec Yanshan Petrochemical, grade LD100AC or LD200; or PetroChina Daqing Petrochemical, grade 2426H; melt flow rate 2.0g / 10min (190℃ / 2.16kg). Linear low-density polyethylene (LLDPE): Sinopec Tianjin Petrochemical, grade DFDA-7042; or ExxonMobil, grade LL1001; melt flow rate 1.8g / 10min (190℃ / 2.16kg). POE elastomer toughening agent: Dow Chemical, brand name ENGAGE 8150 or ENGAGE 8200; or ExxonMobil, brand name EXACT 0201; octene comonomer content 25% to 35%. Activated nano silica: Degussa, brand name AEROSIL R972 (hydrophobicated by DDS); or domestic Wanzai County Huiming Chemical, brand name HB-139; original particle size 16nm, BET specific surface area 110±20 m² / g. Ultrafine activated talc powder: Liaoning Haicheng Jinghua Minerals, brand name HTP-05; or Imerys, brand name MistronVapor; activated by coupling agent, particle size D50≤2μm, and sheet thickness<100nm. Antioxidant 1010: BASF, brand name Irganox 1010; or domestically produced by Sanfeng Chemical Co., Ltd. in Linyi City, Shandong Province, brand name KY-1010. Antioxidant 168: BASF, brand name Irgafos 168; or domestically produced by Sanfeng Chemical Co., Ltd. in Linyi City, Shandong Province, brand name KY-168. High molecular weight hindered amine stabilizer 944: BASF, brand name Chimassorb 944; or domestic Suqian Liansheng, brand name LS-944. Antioxidant zinc composite heat stabilizer: domestic Dalian zinc oxide plant, indirect method nano zinc oxide, particle size 20-40nm. Silane coupling agent KH-560: Nanjing Shuguang Chemical Group, γ-glycidyl etheroxypropyltrimethoxysilane, purity ≥98%. Low-temperature dispersing lubricant: stearamide or erucamide, domestically produced by Jiangxi Hongyuan Chemical Co., Ltd., brand name HY-316. Dispersing brightener: Polyethylene wax or oxidized polyethylene wax, domestic Qingdao Zhongsu, brand name OPE-wax. 4.7 Product Structure Characteristics The mulch film of this invention is an integrated microstructure of LDPE / LLDPE multi-component reinforcement and toughening, with a nominal thickness of 0.015 mm, conforming to the thickness specifications for thickened high-strength mulch films in the national standard GB 13735-2017. The membrane's interior utilizes a POE interface modifier to achieve uniform entanglement and tight fusion of LDPE and LLDPE molecular chains, while simultaneously dispersing uniformly distributed nano-reinforcing particles, forming a stable microstructure of "resin matrix + nanoparticle interpenetrating network". The membrane exhibits a uniform cross-sectional structure, free from stress concentration weak points and surface defects, and exhibits highly balanced mechanical properties in both longitudinal and transverse directions. 4.8 Preparation method The method for preparing the mulch film according to the present invention includes the following steps: Step (1) – Nanofiller activation pretreatment: Activated nano-silica and ultrafine activated talc powder are mixed evenly according to the formula. A measured amount of silane coupling agent KH-560 and dispersant brightener are added. The mixture is activated by high-speed stirring at 68-72℃ for 18-22 minutes to fully complete the surface activation modification of the nanoparticles. After low-temperature drying to remove residual moisture and volatiles, a composite reinforced filler with high dispersibility and high interfacial bonding activity is obtained. When the activation temperature is below 68℃, the ring-opening reaction rate between the epoxy groups of KH-560 and the hydroxyl groups on the surface of nano-SiO2 is insufficient, and the nanoparticles remain hydrophilic (failure example T1: >5μm aggregates appear after activation at 50℃); when the activation temperature is above 72℃, the self-condensation of KH-560 intensifies, and the coupling agent molecules crosslink to form oligomers instead of being grafted onto the surface of the nanoparticles (failure example T2: the effective coupling efficiency decreases after activation at 85℃, and the nominal strain at transverse fracture drops to 620%). When the activation time is less than 18 min, the coupling reaction does not reach equilibrium (failure example T3: 1~3 μm agglomerates appear after 10 min activation); when it is more than 22 min, the coupling agent molecular layer is too thick and the material is subjected to mechanical shear and thermal oxidation (failure example T4: the film is slightly discolored after 40 min activation). Step (2) - Precision pre-mixing of composite additives: The low temperature dispersing lubricant, antioxidant 1010, auxiliary antioxidant 168, high molecular weight hindered amine stabilizer 944, and antioxidant zinc composite heat stabilizer are precisely weighed in proportion and stirred evenly to prepare a highly homogeneous micro-nano additive premix, avoiding problems such as uneven dispersion and local concentration loss caused by direct feeding of each micro-additive, and ensuring the consistency and stability of each functional component of the mulch film system. Step (3) – Resin matrix pretreatment: LDPE resin, LLDPE resin and POE elastomer toughening agent are added to a high-speed mixing device and stirred at high speed for 5-7 minutes at room temperature to fully mix and pre-disperse the resin components, achieving the initial fusion of the multiphase resin matrix. This avoids the problems of layering, phase separation and poor compatibility in traditional blended mulch films from the front-end process. Step (4) – Multi-component blending: The composite reinforcing filler obtained in step (1) and the additive premix obtained in step (2) are added to the resin matrix mixture obtained in step (3) in sequence. The mixture is stirred at high speed for 8-10 minutes at room temperature to uniformly disperse the components. After cooling, it is left to stand for later use. The entire process avoids high-temperature premixing, effectively preventing the premature decomposition and failure of functional additives such as antioxidants and light stabilizers due to overheating during the blending process, and ensuring the chemical integrity and activity stability of each functional component. Step (5) - Melt extrusion blow molding: The blended material obtained in step (4) is fed into the blown film equipment. The barrel temperature is precisely controlled in segments to be 155-175℃. The appropriate screw speed and extrusion pressure are matched with the optimal processing temperature window of LDPE / LLDPE multiphase resin to promote the full plasticization and melting of multiphase resin components and interface fusion. After extrusion through the die head and cooling and shaping by the air ring, a cylindrical film with uniform thickness is obtained.This temperature window represents the optimal range for balancing full plasticization and fusion of the three phases with the stability of the antioxidant system. Below 155℃, LLDPE plasticization is insufficient, resulting in unmelted crystals and flow marks on the film surface (failure example E1: film thickness deviation > ±20% at 135–145℃, unable to produce continuously). Above 175℃, the LDPE molecular chains begin thermal oxidative degradation, increasing the TGA weight loss rate of the hindered amine stabilizer 944 (failure example E2: localized yellowing and charring on the film surface at 185–200℃, tensile load reduced to 3.4N). Above 195℃, the molecular weight (Mw) decreases from ~85kDa to ~65kDa (GPC measurement, decrease >20%), resulting in completely substandard products (failure example E3: severe yellowing and frequent bubble breakage at 195–210℃, unable to produce continuously). Step (6) – Biaxial stretching and leveling / winding: By precisely controlling the blow-up ratio and traction rate, the film is subjected to biaxial stretching and orientation in both the longitudinal and transverse directions. This optimizes the orderly arrangement and orientation of the polymer chains along the stretching direction, effectively improving the nominal strain capacity and flexibility of the film in both longitudinal and transverse directions. After flattening, edge trimming, leveling, and winding, the finished product of the high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film with balanced mechanical properties, excellent weather resistance, and comprehensive indicators fully meets the standards is obtained.
[0005] The technical solution and its beneficial effects of the present invention are further illustrated below through multiple embodiments and comparative examples. The nominal thickness of the membrane in all embodiments and comparative examples is 0.015 mm, and the preparation process parameters are the same unless otherwise specified: Step (1) activation temperature 70℃, activation time 20 min; Step (3) high-speed stirring 6 min; Step (4) high-speed stirring 9 min; Step (5) barrel temperature segmented to 160~170℃. 5.1 Example Example 1 (Optimal Formulation): 82 parts LDPE, 13 parts LLDPE, 1.6 parts POE elastomer toughening agent, 1.4 parts activated nano-silica, 1.2 parts ultrafine active talc, 0.15 parts low-temperature dispersing lubricant, 0.24 parts antioxidant 1010, 0.16 parts auxiliary antioxidant 168, 0.26 parts hindered amine stabilizer 944, 0.20 parts zinc oxide composite heat stabilizer, 0.12 parts silane coupling agent KH-560, and 0.13 parts dispersing brightener. An enhanced agricultural ground cover film was prepared according to the preparation method described in claim 5. Example 2 (Upper Limit Formulation): 85 parts LDPE, 10 parts LLDPE, 1.2 parts POE elastomer toughening agent, 1.0 part activated nano-silica, 1.0 part ultrafine active talc, 0.10 parts low-temperature dispersing lubricant, 0.18 parts antioxidant 1010, 0.12 parts auxiliary antioxidant 168, 0.22 parts hindered amine stabilizer 944, 0.18 parts zinc oxide composite heat stabilizer, 0.10 parts silane coupling agent KH-560, and 0.10 parts dispersing brightener. An enhanced agricultural ground cover film was prepared according to the preparation method described in claim 5. Example 3 (lower limit formulation): 78 parts LDPE, 16 parts LLDPE, 2.0 parts POE elastomer toughening agent, 1.8 parts activated nano-silica, 1.6 parts ultrafine active talc, 0.20 parts low-temperature dispersing lubricant, 0.28 parts antioxidant 1010, 0.20 parts auxiliary antioxidant 168, 0.32 parts hindered amine stabilizer 944, 0.24 parts zinc oxide composite heat stabilizer, 0.14 parts silane coupling agent KH-560, and 0.16 parts dispersing brightener. An enhanced agricultural ground cover film was prepared according to the preparation method described in claim 5. 5.2 Comparative Analysis – Single-Factor Missing Factor Validation To verify the necessity and synergistic effect of the key technical features of this invention, parallel control experiments were conducted using the following comparative examples. Unless otherwise specified, the components and preparation methods in each comparative example are the same as in Example 1. Comparative Example 1 (lacking POE interfacial compatibilizer): The formulation did not include POE elastomer toughening agent; the remaining components and amounts were the same as in Example 1. The effect of POE compatibilization modification on the interfacial compatibility of LDPE / LLDPE and the longitudinal and transverse mechanical balance of the film was verified. Comparative Example 2 (lacking nano-reinforcing fillers): The formulation did not include activated nano-silica and ultrafine activated talc; the remaining components and amounts were the same as in Example 1. The contribution of the nanoparticle synergistic reinforcement system to the tensile and tear loads of the film was verified. Comparative Example 3 (using a single anti-aging agent): The formulation only added antioxidant 1010 (0.50 parts), without adding auxiliary antioxidant 168, hindered amine stabilizer 944, and zinc oxide composite heat stabilizer. The remaining components and dosages were the same as in Example 1. This verified the performance advantages of the five-level synergistic weather protection system compared to traditional single anti-aging agents. Comparative Example 4 (LDPE / LLDPE ratio outside the range): LDPE was adjusted to 90 parts, LLDPE was adjusted to 5 parts (LLDPE dosage was below the lower limit of the claim scope), and the remaining components and dosages were the same as in Example 1. This verified the critical significance of the lower limit of LLDPE dosage. Comparative Example 5 (Commercially Available Ordinary Pure LDPE Mulch Film): A commercially available ordinary pure LDPE agricultural mulch film product with a nominal thickness of 0.015 mm, manufactured by an agricultural film company in Shandong Province. It contains only basic antioxidants and has no LLDPE, no nanofillers, and no POE compatibilization modification. It reflects the industry benchmark level of existing pure LDPE mulch films. Comparative Example 6 (Commercially Available Conventional LDPE / LLDPE Blended Mulch Film): A commercially available conventional LDPE / LLDPE blended agricultural mulch film product with a nominal thickness of 0.015 mm, manufactured by an agricultural film company in Henan Province. The LDPE:LLDPE ratio is approximately 80:20. It has no POE compatibilization modification, no nanofillers, and uses a general-purpose single-component light stabilizer. This reflects the industry benchmark level of existing conventional blended mulch films. 5.3 Orthogonal Synergistic Experiments – Three-Factor Cross-Tests: To systematically verify the synergistic effect among POE compatibility enhancement, nano-reinforcement, and multi-level weather resistance, the following seven orthogonal cross-tests (orthogonal-1 to orthogonal-7) were set up, which, together with Example 1, constitute a complete three-factor, two-level orthogonal experimental matrix. Except for the differences listed in the table, the other conditions are the same as in Example 1. 5.4 Cases of Bidirectional Criticality of Key Components Leading to Negative Failure To demonstrate that the selection of the dosage range of each component has a clear critical significance—that any ratio within the range can achieve the purpose of the invention, while exceeding either end of the range leads to unacceptable degradation of performance—the following failure cases are set up. Except for the differences listed in the table, the other conditions are the same as in Example 1. 5.5 Cases of failure due to critical process parameters The following failure cases verify the critical significance of key process parameters, proving that the selection of process conditions cannot be "determined by routine experiments." Except for the differences listed in the table, the other conditions are the same as in Example 1. Figure 3 Five-dimensional performance radar chart of orthogonal cooperative experiment 5.8 Quantitative Analysis of Synergistic Effects Define the Synergy Index (SI): SI = [E(intact system) - E(completely missing baseline)] / ∑[E(single-factor presence) - E(completely missing baseline)]. The nominal strain at transverse fracture is used as the evaluation index. • POE contribution alone: Orthogonal-6 (weather-resistant only: 530%) - Orthogonal-7 (completely lacking: 510%) = +20 percentage points • Nanoparticle-only contribution: Orthogonal-5 (nanometers only: 550%) - Orthogonal-7 (completely absent: 510%) = +40 percentage points • Weather resistance contribution alone: Orthogonal-4 (POE only: 660%) - Orthogonal-7 (completely lacking: 510%) = +150 percentage points • Simple summation of the three factors: 20 + 40 + 150 = +210 percentage points → Theoretical value 510 + 210 = 720% • Actual improvement of the complete system: Example 1 (795%) - Orthogonal-7 (510%) = +285 percentage points SI = 285 / 210 = 1.36 SI = 1.36 > 1.0, confirming a significant positive synergistic effect between POE compatibilization and nanofillers. After POE improves the interfacial compatibility of LDPE / LLDPE, the dispersion uniformity of nanofillers in the matrix is greatly enhanced. The cycle of "compatibility enhancement → uniform dispersion → dispersion strengthening" forms a positive reinforcement cycle, making the actual effect far exceed the simple summation of the individual contributions of each component. This synergistic effect cannot be reasonably predicted from the simple superposition of existing technologies, and constitutes an important inventive basis for this invention. Figure 4 Quantitative analysis of the Synergy Index (SI) 5.9 Data on performance degradation curves at multiple time points To comprehensively characterize the aging degradation kinetics of the thin film of the present invention, continuous monitoring was conducted at six time points (0h / 100h / 200h / 300h / 400h / 500h) for Examples 1, 3, 5, and 6 (accelerated aging with xenon lamp, according to GB / T16422.2-2014), and the degradation trajectory of key mechanical indicators was recorded. (A) Tensile strength retention decay curve data Table 6: Data on the decrease in tensile strength retention over xenon lamp aging time ★ Comparative Example 5 showed an accelerated inflection point in autocatalytic degradation within 200-300 hours, with the degradation rate surging from 0.138% / h to 0.276% / h. Example 1 showed a stable degradation rate throughout the entire range (0.013-0.027% / h) without an accelerated degradation inflection point. Figure 1 Tensile strength retention rate decay curve with aging time (B) Nominal strain decay curve data of transverse fracture Table 7: Decrease curves of nominal transverse fracture strain with xenon lamp aging time ↓ Comparative Example 5 showed that after 400 hours, the nominal strain at break dropped to 195%, which was below the minimum strain threshold (250%) for mechanized recycling, and the membrane became brittle to the point that it could not be recycled mechanically. Example 1 still showed a strain as high as 728% after 500 hours, far exceeding the safety threshold. Figure 2 Transverse fracture nominal strain decay curve with aging time
[0006] Results Analysis (1) The mechanical properties are comprehensively stable and exceed the national standard, and the formulation range is effective throughout. All mechanical indicators of Examples 1 to 3 comprehensively exceed the mandatory limits of thickened high-strength mulch films in GB 13735-2017, verifying the effectiveness of the formulation range (78-85 parts LDPE, 10-16 parts LLDPE) described in claim 1 throughout. The transverse tensile load of Comparative Example 4 (LLDPE=5 parts, exceeding the lower limit) is only 2.7N, proving the critical significance of the lower limit of LLDPE content (10 parts). Failure examples L1 to L3 further verified the bidirectional criticality of the LLDPE ratio: at 9 parts, the nominal transverse fracture strain is only 630%, which does not meet the national standard requirement of ≥700%; at 20 parts, the processing torque increases by 39%, and crystal points appear on the film surface; at 23 parts, continuous production is no longer possible. (2) POE interface compatibilization is key – cross-validation between Comparative Example 1 and Orthogonal-3. The nominal transverse fracture strain of Comparative Example 1 (without POE) was only 420%, far lower than the 795% of Example 1, with a longitudinal and transverse strain difference of 38%. The nominal transverse fracture strain of Orthogonal-3 (with nano-fillers and weather-resistant materials, but without POE) was also only 420%, consistent with Comparative Example 1. This cross-validation confirms that regardless of how the nanofiller and weather-resistant system are optimized, the lack of POE compatibilization leads to the separation of the LDPE / LLDPE two-phase interface and the resulting severe anisotropy. POE is the decisive factor in achieving longitudinal and transverse mechanical equilibrium. (3) Multi-level synergistic weather protection is the core guarantee for long-term durability. Comparative Example 3 (single AO 1010) had a strength retention rate of only 64.8% after 500h aging, far lower than the 91.5% of Example 1; multi-time point monitoring revealed that its decay rate (0.070% / h) was 4.1 times that of Example 1 (0.017% / h). Orthogonal-1 (with POE + nano, lacking five-level weather resistance) also had a retention rate of only 64.8% after 500h, cross-validating the inherent limitations of a single type of anti-aging agent. The components of the five-level weather resistance system each play their respective roles and are inseparable in the three degradation pathways of photoinitiation (HALS 944, nano ZnO), thermal initiation (AO 1010, AO 168), and catalytic initiation (nano ZnO metal passivation). (4) Sufficient evidence for synergistic effect. Quantitative calculations using orthogonal experiments showed that the synergistic index SI between POE and nanofillers was 1.36 > 1.0, confirming the existence of significant positive synergy. The physical mechanism of this synergistic effect is as follows: POE compatibilization improves the interfacial compatibility of LDPE / LLDPE, enabling the nanofillers to be uniformly dispersed in both phases rather than being enriched only in one phase, thereby extending the dispersion enhancement effect of nanoparticles from local to global. (5) Excellent recyclability. The films in Examples 1-3 maintained their structural integrity after the end of their service life and could be mechanically removed as a whole, with a recycling rate ≥93% (Example 1 ≥95%). Multi-time-point strain decay curves revealed that the nominal strain at break in Comparative Example 5 dropped to 195% after 400 hours of aging, below the minimum strain threshold (250%) required for mechanized recycling, while Example 1 maintained 728% after 500 hours, far exceeding the safety threshold. This quantifies the "recyclability window" of the film of this invention from the perspective of aging kinetics. Beneficial effects of the present invention (1) Multi-component synergistic design based on the material genome concept to achieve performance multiplication. This invention integrates twelve functional materials into a highly synergistic material system, including LDPE (matrix continuity + processability), LLDPE (linear reinforcement + tear resistance), POE (interface compatibilization + dispersion toughening), activated nano-SiO2 (spherical nano-pinning reinforcement), ultrafine active talc (lamellar barrier reinforcement), hindered amine 944 + antioxidant 1010 + antioxidant 168 + nano-ZnO + KH-560 (five-level molecular chain synergistic protection). Orthogonal experiments confirmed that the synergy index SI = 1.36, and each component plays a role at three levels: molecular scale, nanoscale and microscale, achieving a material synergistic effect of "1+1>2". (2) The material design endows the film with the inherent property of "recyclability after retirement" from the source. Molecular-level compatibilization of LDPE / LLDPE / POE provides basic toughness and elongation; a sphere-sheet binary nano-reinforcement system enhances the tear resistance threshold to prevent the accumulation of micro-damage; and a five-layer synergistic weather-resistant protection maximizes the retention of the molecular weight of the polymer chains at the end of their service life. These three material barriers work in a progressive manner. Aging kinetic data confirm that after 500 hours of aging, the nominal strain at break in Example 1 was still as high as 728%, far exceeding the 250% mechanical recycling safety threshold, while the pure LDPE mulch film had dropped to 195% after 400 hours, completely losing its recyclability. This design upgrades "recycling" from a passive post-use treatment to an active property of the material itself. (3) The industrialized material system balances production feasibility and economy. LDPE (78-85 parts) is used as the main material, maximizing its industrial advantages of low cost (approximately 8,000-9,000 RMB / ton), ease of processing, and compatibility with general blown film equipment. LLDPE accounts for only 10-16 parts as reinforcing auxiliary material, and the total amount of POE and nanofillers is controlled within 5 parts. While achieving a significant performance improvement, the total raw material cost only increases by about 15%-20% compared to ordinary LDPE mulch film, far lower than the cost increase of complex process routes such as multilayer co-extrusion, radiation crosslinking, and graft modification. The product yield is high, and no new equipment investment is required. (4) A multi-level synergistic weather-resistant protection system significantly extends service life. The constructed five-level integrated molecular chain protection material system, consisting of "hindered amine free radical cyclic capture (HALS 944) + hindered phenolic main antioxidant (AO 1010) + phosphite auxiliary antioxidant (AO 168) + nano zinc oxide UV shielding and metal passivation + silane coupling agent interface stabilization (KH-560)," comprehensively blocks the breakage of polyethylene molecular chains from three degradation pathways: photo-initiated, thermally initiated, and catalytically initiated. Aging data at multiple time points confirm that Example 1 exhibits a stable decay rate (0.013~0.027% / h) across the entire 500h range, with no autocatalytic degradation inflection point; while pure LDPE shows an accelerated decay inflection point within 200~300h. The actual field service life reaches 13~16 months. (5) Wide range of applicable scenarios and great market expansion potential. The film material of the present invention has stable performance and outstanding cost performance. It can be widely used in the mulching cultivation of field crops such as corn, cotton, soybeans, tobacco, vegetables, and Chinese medicinal materials, as well as facility agriculture. It is also particularly suitable for harsh agricultural environments where traditional mulch films are difficult to handle, such as windy and arid conditions, high altitude and cold, saline-alkali conditions, and large temperature differences between day and night. The industrial application prospects are broad. References [1] State Administration for Market Regulation, Standardization Administration of China. GB 13735-2017 Polyethylene blown agricultural ground covering film [S]. Beijing: China Standards Press, 2017. [2] State Administration for Market Regulation, Standardization Administration of China. GB / T 1040.1-2018 Determination of tensile properties of plastics - Part 1: General principles [S]. Beijing: China Standards Press, 2018. [3] State Administration for Market Regulation, Standardization Administration of China. GB / T 1040.3-2018 Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets [S]. Beijing: China Standards Press, 2018. [4] State Administration for Quality Supervision, Inspection and Quarantine. GB / T 6672-2001 Mechanical Measurement Method for Determination of Thickness of Plastic Films and Sheets [S]. Beijing: China Standards Press, 2001. [5] State Administration for Market Regulation, Standardization Administration of China. GB / T 16422.2-2014 Plastics Laboratory Light Source Exposure Test Methods Part 2: Xenon Arc Lamp [S]. Beijing: China Standards Press, 2014. [6] Department of Science, Technology and Education, Ministry of Agriculture and Rural Affairs. Implementation Plan for Pilot Project of Scientific Use and Recycling of Agricultural Film (Document No. 3 of 2022, Agricultural Office) [Z]. 2022. [7] Yu Liwu, Yang Yingnan, Qiao Fuyong, Wang Li, Ding Xiaofeng, Xu Wei, Guo Chunyun. Study on photoaging behavior and correlation of polyethylene mulch film [J]. Synthetic Materials Aging and Application, 2022, 51(6):5-7. [8] Dong Chungang, Zhang Haifeng, Ma Mengqi, Ji Haojie, Hu Yuexin. Effect of elastomer modulus on structure and properties of polyethylene blends [J]. Modern Chemical Industry, 2022, 51(5):1093-1098. [9] Wu Lei, Zhang Gangpeng, Xu Huitong, Maimaitijiang Yimiti. Preparation of anti-aging masterbatch for drip irrigation tape from recycled mulch film and performance testing [J]. Plastics Industry, 2023, 51(3):121-128.
[10] Wang Lixia, Zhou Baokai, Shi Miaolei, Wang Shiwei, Li Qian. Structure and properties of ultra-high molecular weight polyethylene / polyolefin elastomer blends [J]. Polymer Materials Science and Engineering, 2022, 38(4):73-79.
[11] Huo Chang'an, Shi Xiaowei, Xie Jiong, Wang Xinlong. Study on LDPE and LLDPE blended resin film [J]. Modern Plastics Processing and Application, 2017, 29(4):19-21.
[12] Lin Cheng. Study on the structural performance evolution of polyethylene film functionalization preparation process and verification of mulch film [D]. Guangzhou: South China University of Technology, 2023.
Claims
1. A high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film, characterized in that, It is prepared from the following raw materials in parts by weight: low-density polyethylene resin (LDPE): 78-85 parts; linear low-density polyethylene resin (LLDPE): 10-16 parts; POE elastomer toughening agent: 1.2-2.0 parts; activated nano silica: 1.0-1.8 parts; ultrafine activated talc powder: 1.0-1.6 parts; low-temperature dispersing lubricant: 0.10-0.20 parts; antioxidant 1010: 0.18-0.28 parts; auxiliary antioxidant 168: 0.12-0.20 parts; high molecular weight hindered amine stabilizer 944: 0.22-0.32 parts; zinc oxide composite heat stabilizer: 0.18-0.24 parts; silane coupling agent KH-560: 0.10-0.14 parts; dispersing brightener: 0.10-0.16 parts; The film simultaneously meets all of the following performance indicators: (a) longitudinal tensile load ≥3.6N, transverse tensile load ≥3.2N; (b) longitudinal nominal strain at break ≥550%, transverse nominal strain at break ≥700%; (c) longitudinal right-angle tear load ≥1.6N, transverse right-angle tear load ≥1.8N; (d) after 500h xenon lamp accelerated aging test (according to GB / T 16422.2-2014), the tensile strength retention rate is ≥85%; (e) after at least 13 months of field service, the film can be completely peeled off and continuously rolled up by rake-type or shovel-type mechanized recycling equipment, with a recycling rate ≥90%.
2. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that, It is prepared from the following raw materials in parts by weight: low-density polyethylene resin (LDPE): 82 parts; linear low-density polyethylene resin (LLDPE): 13 parts; POE elastomer toughening agent: 1.6 parts; activated nano silica: 1.4 parts; ultrafine active talc powder: 1.2 parts; low-temperature dispersing lubricant: 0.15 parts; antioxidant 1010: 0.24 parts; auxiliary antioxidant 168: 0.16 parts; high molecular weight hindered amine stabilizer 944: 0.26 parts; zinc oxide composite heat stabilizer: 0.20 parts; silane coupling agent KH-560: 0.12 parts; dispersing brightener: 0.13 parts.
3. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that: The low-density polyethylene resin is a special grade resin for agricultural mulch film, with a melt flow rate of 2.0 g / 10 min; the linear low-density polyethylene resin is a film-grade polyethylene resin, with a melt flow rate of 1.8 g / 10 min; the activated nano-silica and ultrafine activated talc powder have a particle size of 30-50 nm and are surface activated by silane coupling agent KH-560, resulting in hydrophobic surface modification, uniform dispersion, and no agglomeration.
4. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that: The film is an integrated microstructure of LDPE / LLDPE multi-component reinforcement and toughening, with a nominal thickness of 0.015 mm. The film contains a composite microstructure in which LDPE and LLDPE molecules are uniformly entangled and nanoparticles are dispersed.
5. A method for preparing a high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Activation pretreatment of nanofillers: Activated nano silica and ultrafine active talc powder are mixed evenly according to the formula, and a metered amount of silane coupling agent KH-560 and dispersant brightener are added. The mixture is activated by high-speed stirring at 68-72℃ for 18-22 minutes to fully complete the surface activation modification. The residual moisture and volatiles are removed by low-temperature drying to obtain a composite reinforced filler with high dispersibility and high interfacial bonding activity. (2) Precision pre-mixing of composite additives: Weigh the low-temperature dispersing lubricant, antioxidant 1010, auxiliary antioxidant 168, high molecular weight hindered amine stabilizer 944 and zinc oxide composite heat stabilizer in a precise proportion and stir evenly to prepare a high homogeneous micro-nano additive premix. (3) Pretreatment of resin matrix: LDPE resin, LLDPE resin and POE elastomer toughening agent are put into a high-speed mixing device and stirred at high speed for 5 to 7 minutes at room temperature to fully mix and pre-disperse each resin component and achieve the initial fusion of multiphase resin matrix. (4) Multi-component blending: In the resin matrix mixture obtained in step (3), the composite reinforcing filler obtained in step (1) and the additive premix obtained in step (2) are added in sequence. The mixture is stirred at high speed for 8 to 10 minutes at room temperature to ensure that the components are evenly dispersed. After cooling, it is allowed to stand for later use. (5) Melt extrusion blow molding: The blend material obtained in step (4) is fed into the blown film equipment. The barrel temperature is precisely controlled in segments to be 155-175℃ to promote the full plasticization and melting of the multiphase resin components and the fusion of the interface. After extrusion through the die head and cooling and shaping by the air ring, a cylindrical film with uniform thickness is obtained. (6) Biaxial stretching and leveling and winding: By precisely controlling the blow-up ratio and traction rate, the film is subjected to biaxial stretching and orientation in the longitudinal and transverse directions to optimize the orderly arrangement and orientation of polymer chains along the stretching direction. After flattening, edge trimming, leveling and winding, the high-toughness, aging-resistant and recyclable reinforced agricultural ground cover film is obtained.
6. The preparation method according to claim 5, characterized in that: The melt extrusion blow molding process described in step (5) can achieve full plasticization and fusion of LDPE and LLDPE multiphase resins, without delamination or interface separation. While ensuring good film formability, it does not affect the surface smoothness and thickness uniformity of the film.
7. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that: The material system of the film, composed of twelve raw materials, works through a synergistic effect of four material science mechanisms: differentiated compounding of matrix resin, compatibilization of elastomer interface, synergistic reinforcement of binary nanomaterials, and five-layer synergistic weather resistance protection. This allows the film to meet the following recyclability conditions after 13-16 months of field service: the film maintains a continuous and intact shape, without penetrating cracks or brittle areas; the residual longitudinal tensile load is not less than 60% of the initial value; the nominal longitudinal fracture strain is not less than 50% of the initial value; it can be completely peeled off and continuously wound up by rake-type or shovel-type mechanized recycling equipment, with no breakage or fragment loss during the peeling process, and a recovery rate of ≥95%.
8. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that: After undergoing a 500-hour accelerated aging test under xenon lamp, the film retains a tensile strength of ≥91.5%, and under actual field conditions, its effective service life is 13–16 months.
9. The high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to claim 1, characterized in that: After the film has been used for a period of time, the film structure is intact, the strength is uniform, and there are no defects such as embrittlement or breakage. It can be peeled off and recycled as a whole, with a recovery rate of ≥95%.
10. The application of the high-toughness, aging-resistant, and easily recyclable reinforced agricultural ground cover film according to any one of claims 1 to 9 in mulching cultivation in harsh agricultural environments, characterized in that, The harsh agricultural environment refers to at least one of the following: windy and arid areas, high-altitude and cold areas, saline-alkali land, areas with a diurnal temperature range of ≥20℃, or plateau areas with an altitude of ≥2000 meters.
11. The application according to claim 10, characterized in that: After the complete growing season (≥12 months) of mulched cultivation, the film maintains a continuous and intact shape, without penetrating cracks or powdery and brittle areas, and retains a residual longitudinal tensile load of not less than 60% of the initial value. It can be completely peeled off and continuously rolled up by rake-type or shovel-type mechanized recycling equipment. There is no breakage or fragment shedding during the peeling process, and the recycling rate is ≥90%.